Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24065432
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Key Genes and Therapeutic Molecular Modelling to Explain the Association between Porphyromonas gingivalis (P. gingivalis) and Alzheimer’s Disease (AD)

Abstract: The association between Porphyromonas gingivalis (P. gingivalis) and Alzheimer’s disease (AD) remains unclear. The major aim of this study was to elucidate the role of genes and molecular targets in P. gingivalis-associated AD. Two Gene Expression Omnibus (GEO) datasets, GSE5281 for AD (n = 84 Alzheimer’s, n = 74 control) and GSE9723 (n = 4 P. gingivalis, n = 4 control), were downloaded from the GEO database. Differentially expressed genes (DEGs) were obtained, and genes common to both diseases were drawn. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…As an outcome of docking, it was revealed that the receptors and ligands showed minimum binding energy (-ΔG), leading to the prediction of probable drug ligands. Further, the docking score was critically analyzed and visualized using Biovia Discovery Studio [22], followed by molecular dynamics simulation (MD) with iMOD [23].…”
Section: Screening Of Compounds and Ligand Preparationmentioning
confidence: 99%
“…As an outcome of docking, it was revealed that the receptors and ligands showed minimum binding energy (-ΔG), leading to the prediction of probable drug ligands. Further, the docking score was critically analyzed and visualized using Biovia Discovery Studio [22], followed by molecular dynamics simulation (MD) with iMOD [23].…”
Section: Screening Of Compounds and Ligand Preparationmentioning
confidence: 99%
“…Using gene expression data and bioinformatics tools, the researchers identified common genes between P. gingivalis infection and AD and performed in silico molecular modeling to identify potential drug candidates targeting these genes. This study highlights the potential for integrating omics datasets and computational approaches to elucidate complex disease associations and discover novel therapeutic opportunities [3].…”
mentioning
confidence: 99%